Effect of the SARS COV-2 virus on diabetes symptoms, diagnostics, and treatment - Anna Jaremek; Joanna Kępa; Norbert Kandefer; Michał Wyszkowski; Aleksandra Grabarczyk; Anna Pawlak; Sylwia Grad; Małgorzata Gregorek; Paweł Gregorek (Kazimierz Wielki University, 2023)
Because COVID-19 has been recognised as one of the most important pandemics in the history of humankind, in recent years many scientists have investigated the effect of the disease on various aspects of mental and physical human health. This article presents a literature review regarding the effect of SARS CoV-2 infection on the symptoms, diagnostics, and treatment of diabetes. It discusses the effect of infection with virus SARS-CoV-2 on the course of type 1 and type 2 diabetes as well as the frequency of occurrence of the disease in patients affected by COVID-19. Moreover, it presents information on the pharmacotherapy and way of providing services by doctors during the pandemic. According to the literature, infection with virus SARS CoV-2 causes a general inflammation of the organisms and numerous metabolic and hormonal disturbances, and therefore affects the course of diabetes. It may lead not only to serious metabolic complications in the course of early diabetes, but also to the development of the disease. It was determined that infection with COVID-19 in diabetes patients (mainly type 2) increases the risk of complications (such as acute respiratory failure, multi-organ failure, and death).